Improving testing for hepatitis B before treatment with rituximab. Issue 10 (October 2016) - Dyson, Jessica K.; Jopson, Laura; Ng, Sarah; Lowery, Matthew; Harwood, Jayne; Waugh, Sheila; Valappil, Manoj; McPherson, Stuart
Abstract : Aims/Objectives/Background: Individuals with current or previous infection with the hepatitis B virus (HBV) can experience viral reactivation when treated with immunosuppression. Rituximab, an anti-CD20 antibody used to treat many diseases, has potent immunosuppressant effects with a high risk of causing HBV reactivation. Reactivation can range from elevated liver enzymes to acute severe hepatitis with liver failure and a significant mortality risk. HBV screening and appropriate use of prophylactic antiviral therapy can prevent reactivation. This work describes the introduction of a local policy for HBV testing in patients before rituximab treatment and assesses its impact. Methods and Results: A baseline review (before policy introduction) of 90 patients showed that only 21 (23%) had hepatitis B surface antigen (HBsAg) and 17 (19%) had hepatitis B core antibody (anti-HBcAb) tested before receiving rituximab. Following introduction of the policy (on the basis of international guidelines), improved laboratory reporting protocols and targeted education sessions, two further reviews of HBV testing rates among patients being initiated onto rituximab were performed. There was a marked increase in pre-rituximab testing for HBsAg from 23 to 79% and for anti-HBcAb from 19 to 78%. Throughout the study period, a total of one (0.8%) HBsAg-positive and six (4.7%) anti-HBcAb-positive patients were identified. Conclusions: This work clearly indicates that simple strategies can markedly improve appropriate HBV screening. In our cohort, 6% (of whom only 43% had recognized HBV risk factors) required antiviral prophylaxis, which emphasizes the importance of universal screening before rituximab. Reinforcement of the guidelines and ongoing education is needed to further increase testing rates.